Exposure and knowledge on peanut aflatoxin B1 among urban consumer in Jakarta, Indonesia - Dwi Nastiti Iswarawanti; Tegar Prakasa Putra Masloman; Drupadi HS Drupadi HS (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Groundnut (Arachis hypogaea L), an important food in the Indonesian diet, has been reported to be contaminated with the carcinogenic Aflatoxin B1. However, research on consumer knowledge of and exposure to AfB1 from peanuts in Indonesia is limited. This study aimed to assess the exposure to aflatoxin B1 (AfB1) in peanuts consumed by urban Jakarta and their knowledge of aflatoxin risk. This observational study had a cross-sectional design and involved 192 randomly selected respondents. Peanut intake frequency was measured using a semi-quantitative FFQ instrument. Questionnaires were used to collect data regarding knowledge and income. The AfB1 content was analyzed using HPLC. Pearson Chi-Square test was used for analysis. The results showed that AfB1 contaminants were present in all the samples. Respondents who frequently consumed high amounts of peanuts and processed products were exposed to AfB1, with a median of 22,55 ppb bb/day. There were no significant relationships between knowledge and AfB1 exposure (p= 0,874), age (p= 0,884), or income (p= 0,355). In conclusion, aflatoxin B1 exposure was high in urban areas. No relationship was found between knowledge of and exposure to AfB1 peanuts. Inter-sectoral strengthening of the empowerment and control of aflatoxin exposure is needed, as are economic and health impact studies on AfB1 exposure.